2014
DOI: 10.1177/0284185114561821
|View full text |Cite
|
Sign up to set email alerts
|

Locations of lesser tuberosity cysts and their association with subscapularis, supraspinatus, and long head of the biceps tendon disorders

Abstract: Cysts within the lesser tuberosity were less common than cysts adjacent to it. LHBT and subscapularis tendon disorders were more frequently found in patients with more than one cyst within and/or adjacent to the lesser tuberosity. In addition, cysts within the lesser tuberosity were associated with LHBT disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…In previous reports, changes at the lesser tuberosity such as lesser tuberosity cysts and cortical irregularities were associated with subscapularis tendon tears (1,(13)(14)(15). However, the data acquired in this study failed to show that the lesser tuberosity changes, including cyst formations and bone marrow edema, would be reliable MRI features indicating the presence of a subscapularis tendon tear.…”
Section: Discussioncontrasting
confidence: 77%
“…In previous reports, changes at the lesser tuberosity such as lesser tuberosity cysts and cortical irregularities were associated with subscapularis tendon tears (1,(13)(14)(15). However, the data acquired in this study failed to show that the lesser tuberosity changes, including cyst formations and bone marrow edema, would be reliable MRI features indicating the presence of a subscapularis tendon tear.…”
Section: Discussioncontrasting
confidence: 77%
“…The strong relationship of the cysts with the rotator cuff tendons, as well as the TMCs with the subscapularis tendon, was previously reported by several studies [ 22 , 23 , 34 ]. In the current study, the TMC was fewer in the operated shoulder than in the healthy ones.…”
Section: Discussionsupporting
confidence: 67%
“…The SCI syndrome has been investigated a number of times in a number of studies with a number of parameters. There have been reported results opposite to one another, even in papers with quite similar study designs [ 2 , 6 , 7 , 9 , 17 , 22 , 23 ]. The instinct was mostly towards the existence of this syndrome which paves the way for subscapularis tendon tear.…”
Section: Discussionmentioning
confidence: 99%
“…Celikyay et al 49 found that the presence of cystic change on or around the lesser tuberosity was strongly associated with LHBT and subscapularis tears. Razmjou et al 46 examined patients with associated rotator cuff disease undergoing arthroscopy and noted 100% sensitivity of MRI for detection of subluxation or dislocation of the LHBT.…”
Section: Introductionmentioning
confidence: 99%